1991
DOI: 10.1111/j.1365-2559.1991.tb00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia associated with a composite lymphoma

Abstract: We report a case of composite lymphoma heralded by a hyper-eosinophilia syndrome. Combination of immunophenotyping and gene rearrangement analysis allowed us to confirm malignancy and to detect a minor oligoclone B within a malignant T-cell predominant population. No evidence of retroviral infection was found using western blot and gene amplification techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Another possibility is the presence of two monoclonal populations bearing morphological abnormalities, as reported in the very rare composite B cell and T cell lymphoma 32, but much more frequently in AILT 22, 33 in which a monoclonal IgH rearrangement was detected in 20% of cases by Southern blot 34, 35. AIL has been considered as a heterogeneous disease associated with immunodeficiency, in which B cell or T cell clones may develop 22, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is the presence of two monoclonal populations bearing morphological abnormalities, as reported in the very rare composite B cell and T cell lymphoma 32, but much more frequently in AILT 22, 33 in which a monoclonal IgH rearrangement was detected in 20% of cases by Southern blot 34, 35. AIL has been considered as a heterogeneous disease associated with immunodeficiency, in which B cell or T cell clones may develop 22, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Many cases are associated with viral infection especially with EBV . Of interest the presence of EBV has been demonstrated within one or both of the components . Thus, it could be speculated that virus may induce transformation of two different neoplastic clones.…”
Section: Discussionmentioning
confidence: 99%
“…While many of these cases are composed of Hodgkin's and non‐Hodgkin's components, 5–14 others represent different types of non‐Hodgkin's lymphoma from the same lineage 15–18 . Examples of CTBL have also been documented, 19–40 and the components involved in these CTBLs have been shown to vary from one case report to another.…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been proposed in an attempt to explain how these clonal proliferations co‐exist. For example, the presence of the Epstein‐Barr virus (EBV) has been demonstrated within one or both of the components in a variety of studies, 7,13,19,20,25,37,39 and EBV has been suggested to be a possible etiological agent involved in the development of the B‐cell component within an already‐existing T‐cell lymphoma. Other clinical conditions, such as rheumatoid arthritis and celiac disease, are thought to predispose patients to the development of CTBL.…”
mentioning
confidence: 99%